The reproduction of `coaching culture`: a Bourdieusian analysis of a formalised coach mentoring programme - Leeder, T.; Cushion, C. (Sports Coaching Review, 2020)
Despite its positive rhetoric, formalised coach mentoring can be problematic due to the institutional agendas of National Governing Bodies (NGB), with mentoring functioning as a method to reproduce organisational cultures and beliefs. This research attempted to explore this issue in greater depth by critically analysing a formalised coach mentoring programme. Fourteen mentors and four mentees participated in semi-structured interviews to discuss their experiences of an NGB`s formalised mentoring programme. Analysed through a Bourdieusian lens, the findings present formalised coach mentoring as a source of cultural reproduction, where mentors embodied a group habitus that reinforced the NGB`s dispositions and beliefs towards coaching practice. Mentors strived to inculcate mentees and rework their habituses to align with the field`s doxa through a process of pedagogic action, with symbolic capital proving influential in reproducing coaching ideologies. NGBs should begin to critically analyse their coach mentoring provision to maximise opportunities for mentee learning and development.